IMPROVING STUDENT'S VOCABULARY BY USING PICTURES AT THE FOURTH YEAR OF SDN 3 NGABEYAN KARTASURA IN 2007/2008 ACADEMIC YEAR - SUSWATI , WAHYU (2007)
The objectives of this research are to describe the implementation of teaching vocabulary using pictures, the improving vocabulary and the comment of the fourth year students of SDN 3 Ngabeyan Kartasura in 2007/2008 Academic Year. The object of this study is teaching vocabulary using pictures to elementary students at the fourth year of SDN 3 Ngabeyan Kartasura in 2007/2008 academic year. The writer employs Classroom Action Research and the subject is the students of the elementary school. The first step of action research is planning. The second step is action. The third step is observing, and the last step is the writer tries to reflect the result of the previous step. The method of collecting data is in the form of test, observation, and interview. The technique for analyzing data involves reducing the data, displaying the data, drawing conclusion and proposing suggestion. Based on the analysis, the result of the evaluation shows that in the pre-test the highest score is 70 and lowest score is 40, and the mean score is 57.27. In the post-test, the highest score is 90 and the lowest score is 40, the mean score is 70.90. The increasing score from pre-test to post-test is about 13.63. From the observation, it indicates that students' response with the technique is good. They became active in teaching learning process, and it can be increased their vocabulary achievement.